2019
DOI: 10.3847/1538-4357/aafc5f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas on Formation and Evolution of Stellar Bars and Nuclear Rings in Disk Galaxies

Abstract: We run self-consistent simulations of Milky Way-sized, isolated disk galaxies to study formation and evolution of a stellar bar as well as a nuclear ring in the presence of gas. We consider two sets of models with cold or warm disks that differ in the radial velocity dispersions, and vary the gas fraction f gas by fixing the total disk mass. A bar forms earlier and more strongly in the cold disks with larger f gas , while gas progressively delays the bar formation in the warm disks . The bar formation enhances… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 125 publications
14
86
0
Order By: Relevance
“…In agreement with similar computational works (e.g. Shin et al 2017;Sormani et al 2018a;Seo et al 2019), we found that most of the gas in the CMZ is located in a dense ring-like structure. Such a ring forms in response to the presence of a bar in our Galaxy.…”
Section: Introductionsupporting
confidence: 93%
“…In agreement with similar computational works (e.g. Shin et al 2017;Sormani et al 2018a;Seo et al 2019), we found that most of the gas in the CMZ is located in a dense ring-like structure. Such a ring forms in response to the presence of a bar in our Galaxy.…”
Section: Introductionsupporting
confidence: 93%
“…This is in agreement with the results of Kim et al (2012a), who use hydrodynamic simulations. Recently, Seo et al (2019) found through threedimensional simulations that rings are very small when they first form and grow in size over time. These authors found that the size of the CNR depends on the pattern speed, the central mass concentration and the bar strength.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inward flow of gas, barred galaxies often host intense nuclear star formation or starbursts, often taking the form of nuclear rings of super star clusters (SSCs; e.g., Athanassoula 1984;Buta & Combes 1996;Buta 1999;Böker et al 2008;Comerón et al 2010), as predicted by simulations (Athanassoula 1992;Shlosman 2002;Regan & Teuben 2003;Li et al 2015;Sormani et al 2018;Seo et al 2019). Star formation in barred galaxies can serve as a sink E-mail: dcohen@astro.ucla.edu of the inwardly drifting gas, thus preventing this gas from reaching a central supermassive black hole.…”
Section: Introductionmentioning
confidence: 99%
“…Young SSCs are likely responsible for the multi-phase, large-scale galactic winds observed in starburst galaxies (e.g., Heckman 2001). Hydrodynamic simulations of barred galaxies find that such intense feedback can shape the growth of galactic bulges (e.g., Renaud et al 2013;Athanassoula et al 2013;Carles et al 2016;Li et al 2015;Seo et al 2019). AGN feedback from an accreting SMBH can also regulate star formation in the galactic center and its host bulge (e.g., Robichaud et al 2017).…”
Section: Introductionmentioning
confidence: 99%